Kidney Transplantation From a Donor With Sickle Cell Disease. Issue 2 (21st October 2016) - Rossidis, A.; Lim, M. A.; Palmer, M.; Levine, M. H.; Naji, A.; Bloom, R. D.; Abt, P. L.
Abstract : In the United States, >100 000 patients are waiting for a kidney transplant. Given the paucity of organs available for transplant, expansion of eligibility criteria for deceased donation is of substantial interest. Sickle cell disease (SCD) is viewed as a contraindication to kidney donation, perhaps because SCD substantially alters renal structure and function and thus has the potential to adversely affect multiple physiological processes of the kidney. To our knowledge, transplantation from a donor with SCD has never been described in the literature. In this paper, we report the successful transplantation of two kidneys from a 37‐year‐old woman with SCD who died from an intracranial hemorrhage. Nearly 4 mo after transplant, both recipients are doing well and are off dialysis. The extent to which kidneys from donors with SCD can be safely transplanted with acceptable outcomes is unknown; however, this report should provide support for the careful expansion of kidneys from donors with SCD without evidence of renal dysfunction and with normal tissue architecture on preimplantation biopsies. Abstract : The authors report the successful transplantation of two kidneys from a donor with sickle cell disease and discuss expanding the donor pool with selective utilization of donors with this condition.